The Effect of Imprint and Disturb on Switching Process Based on Poly(vinylidene fluoride-trifluoroethylene) Copolymer Thin Films. Issue 1 (26th January 2016) - Du, Xiaoli; Zhao, Manping; Chen, Guanglong; Ji, Xin; Zhang, Xiuli
Abstract : The simultaneous effect of disturbance and imprint on the polarization switching behaviors of ferroelectric poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)) thin films has been investigated. The results show that the switching characteristics are affected obviously by the imprint as well as the disturbing process. The switching characteristics are well analyzed using the "single read-dual integration" pulse protocol. It is found that the decrease of M-value ("M-value" model is defined as the differences between a switching and a non-switching polarization) with disturb is much faster than that of the pure imprint both before and after fatigue. This result is useful for the design of the related ferroelectric devices.